DANA BANTUAN KEUANGAN PARTAI POLITIK DI SURAKARTA, SUDAHKAH TRANSPARAN DAN AKUNTABEL? - Titik Setyaningsih; Andi Asrihapsari; Doddy Setiawan (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
This study aims to explore transparency and accountability of political parties in Surakarta. This study uses a qualitative method. Data were gathered through focus group discussion. The findings show that political parties do not understand financial report of this entity’s financial assistance under PSAK 45 and they use simple bookkeeping. Political parties’s financial assistance is not audited by external auditor and there are some audit findings. The transparency principle is not achieved because financial report only for internal parties. This study raises one interesting result that political parties need the role of accountant to make their reports more accountable.